2011
DOI: 10.1007/s00198-011-1621-2
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal findings in children recently initiating glucocorticoids for the treatment of nephrotic syndrome

Abstract: Introduction-Vertebral fractures are an under-recognized complication of childhood glucocorticoid-treated illnesses. Our goal was to study the relationship among glucocorticoid exposure, lumbar spine areal BMD (LS BMD) and vertebral shape in glucocorticoid-treated children with new-onset nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 39 publications
(50 reference statements)
3
70
1
Order By: Relevance
“…Through prospective study, we previously described an inverse relationship between lumbar spine bone mineral density (LS BMD) Z-scores and short-term GC therapy in pediatric GCtreated NS [9]. After a median of 18 days following GC initiation, every 1 mg/m 2 increase in GC therapy (prednisone equivalents) was associated with a decrease in spine BMD Z-score of almost 0.4 standard deviation (SD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through prospective study, we previously described an inverse relationship between lumbar spine bone mineral density (LS BMD) Z-scores and short-term GC therapy in pediatric GCtreated NS [9]. After a median of 18 days following GC initiation, every 1 mg/m 2 increase in GC therapy (prednisone equivalents) was associated with a decrease in spine BMD Z-score of almost 0.4 standard deviation (SD).…”
Section: Introductionmentioning
confidence: 99%
“…Feber et al [9] found that 8% of children with GC-treated NS and short-term GC exposure (maximum 37 days) had asymptomatic prevalent VF. On the other hand, a recent report described painful moderate VF in a young boy with NS following 5 years of intermittent GC therapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…The study subjects were children with underlying diseases who had several weeks of exposure to glucocorticoids and some of whom had exposure to other bone-toxic medications [24][25][26]. Individuals with impaired limb function were excluded from the study and there is no reason to expect that the underlying conditions or drugs would selectively alter the dominant to nondominant BMC ratio at younger ages.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were participants in the Canadian Steroid-associated Osteoporosis in the Pediatric Population (STOPP) research initiative [24][25][26]. We studied those STOPP subjects from seven research sites for whom whole body dual-energy x-ray absorptiometry (DXA) was available, who completed handedness evaluations, and who had no significant limitations to limb use.…”
Section: Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation